Hubungan Antara Pengetahuan dan Tingkat Depresi Klien Kanker Serviks Di Ruang Kandungan Rumah Sakit Pelni Jakarta - Suhatridjas; Buntar Handayani; Ricky Riyanto Iksan (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Currently, cervical cancer is still a women's health problem in Indonesia. A cancer diagnosis is one of the stressors that can trigger psychiatric disorders and which often arises is anxiety and depression. This research aims to determine the relationship between the level of knowledge about cervical cancer with the level of depression in people living with cervical cancer at Pelni Hospital in Jakarta. This research method is observational analytic with a cross-sectional approach. The population is all women with cervical cancer in Pelni Hospital Jakarta in the October-November range of 20 people. A sample of 19 respondents who met the criteria was taken using the simple random sampling method with an instrument in the form of a Beck Depression Inventory questionnaire. The data obtained were tested using the Spearman Rank with significance level  = 0.05. The results of the 19 respondents who had cervical cancer, nearly half of the respondents (47.4%) had less knowledge and (44.4%) experienced mild depression—based on the Spearman rank correlation test, obtained  = 0.024 < = 0.05, meaning that there is a relationship between the level of knowledge about cervical cancer with the level of depression in people living with cervical cancer. The conclusion of this study is that almost half of the respondents in Pelni Jakarta Hospital have less knowledge and experience mild depression. For this reason, it is hoped that health workers will always provide informative support in the form of education, promotion, and counseling for patients with cervical cancer. Conclusion: After researching at Pelni Hospital in Jakarta about the level of knowledge about cervical cancer with the level of depression in cervical cancer patients found: patients with cervical cancer in Pelni Jakarta Hospital almost half have less education. Patients with cervical cancer in Jakarta Pelni Hospital nearly half experienced mild depression. The level of knowledge about cervical cancer related to the level of depression in people with cervical cancer in Pelni Jakarta Hospital.